Metropolitan governance and sanitation policy: path dependences in Greater São Paulo - Aversa, Marcelo; Oliveira, Vanessa Elias de (Pontifícia Universidade Católica de São Paulo, 2021)
This paper applies the concepts of path dependence and critical juncture to intergovernmental relations established between municipalities and the state in the metropolization process of São Paulo (1940s), as a methodology of historical institutional analysis of sanitation utilities in the Greater São Paulo area. From the analysis of municipal and state legislations, we verified the historical institutional development of Sabesp and the consolidation process of the path dependence of the interdependent provision of sanitation services between municipal (local) and state (regional) operators during the Greater São Paulo metropolization process. This institutional path dependence remains nowadays in the Metropolitan Region of São Paulo, as a source of legal conflicts through which Sabesp has been expanding its operations in metropolitan municipalities.